AB0484 Identification of Clinical and Serologic Factors Associated with Neutropenia in Patients with Systemic Lupus Erythematosus. (15th July 2016) - Chung, M.K.; Jeon, H.; Kim, S.H.; Kim, I.J.; Lee, J.
Abstract : Background: Hematologic manifestations are common in systemic lupus erythematosus (SLE). Lymphopenia is most commonly found among leukopenia, but neutropenia is also found in about 50–60% of SLE patients. Most patients experience mild neutropenia while less than 5% of those experience moderate to severe neutropenia which can increase susceptibility to recurrent infection. Although it is crucial to understand risk factors associated with neutropenia in SLE patients, there is a paucity of clinical data regarding neutropenia in patients with SLE. Objectives: This study was performed to identify the clinical and serologic factors that are associated with neutropenia in patients with systemic lupus erythematosus (SLE). Methods: A total 160 admissions of 85 SLE patients between 2006 and 2013 were retrospectively reviewed. Neutropenia was defined as absolute neutrophil count (ANC) below 1, 500/mm 3 . Baseline characteristics of the patients were compared between patients who experienced neutropenia and those without. Clinical and serological factors related to neutropenia episode during admission were analyzed using generalized estimating equation (GEE) and multivariate analysis. Results: Thirty two (37.6%) patients experienced neutropenia, and neutropenia episode was found in 35 (21.9%) of admissions. Most of the neutropenia episodes were mild to moderate. Severe neutropenia of ANC<500/ mm 3 occurred in 14.3% of the cases. Patients with neutropenia had higher frequencies of ANA (100.0 vs 86.8%, P =0.042) and anti-dsDNA (87.5 vs 60.4%, P =0.008), and satisfied more SLE classification criteria at the time of the diagnosis than those without (4.8 vs 4.1, P =0.014) Clinical characteristics at admission such as comorbidities, concomitant medications, and SLEDAI were not different between admissions with and without neutropenia episode. Anemia, leukopenia, thrombocytopenia and low complement levels were frequently associated with neutropenic episodes. Co-existence of chronic kidney disease (OR, 16.91; 95% confidence interval (CI), 2.09–136.6; P =0.008) and Sjögren's syndrome (OR, 6.48; 95% CI, 1.46–28.66; P =0.014) was associated with increased risk of developing neutropenia. Conclusions: This study demonstrates that most of neutropenia in SLE patients occur as part of hematologic and immunologic abnormalities. SLE patients with renal damage and Sjogren's syndrome should be closely monitored for development of neutropenia. Disclosure of Interest: None declared